THE MINING INDUSTRY OF GREECE AND THE PRESS - Κιτσόπουλος Κ.; Γιαννούλης Χ.; Χαϊδευτού Ε. (Bulletin of the Geological Society of Greece, 2004)
The present work in/estigates the ongoing development and the shaping of the relationship of the Mining Industry of Greece with the Press, mainly in national and in some cases in local environment too. The time span of this investigation covers the period form the mid 80’s to the year 2000. The paper covers most of the main and traditional mining commodities of Greece. Following an introduction of the industry, the results of the assessment of 178 articles are presented for the commodities studied. The assessment was carried out in terms of the number of articles referred to each commodity, the coverage (national or local) by the publishing agent, usually a newspaper, the "geography" of the articles, the existence of an author signing each article or not and his/her specialty, the positive or the negative attitude and the relevant image which is pictured by the article, the soundness and the validity of the information given, and the reference in other relevant issues such as the environment, financial and political matters, legislation etc.